Community policing’s dark Uuderbelly - Müller, Markus-Michael (Police and state crime in the Americas, 2024)
Zooming in on community-oriented policing programs (COP) in Guatemala, Brazil and Haiti, this chapter argues that far from moving local policing toward a more democratic and less violent form of security provision, COP efforts exacerbate historically grounded forms of violent order-making in and through which those at the margins of Latin American societies continue to be policed not as right-bearing citizens but as society’s undesirable “other.” Moving beyond portrayals of these developments as exclusively local phenomena, the chapter places these practices within their transnational surroundings, including the changing dynamics of globally dominant security epistemologies, and their powerful US imprint, through which marginalized communities in Latin America are rendered legible as breeding grounds for existential threats to lawful citizens, states and hemispheric security alike.